Interview of Norbert Untersteiner by Brian Shoemaker - Untersteiner, Norbert, 1926- (Byrd Polar Research Center Archival Program, 2007)
Key Individuals Mentioned 1. His father, _____ Untersteiner, M.D.—p.1, 2, 3 2. Richard Fensterwalter—p.7 3. Professor Viatorres—p.7 4. Professor Schotts—p.7 5. Professor Heinz von Ficker—p.8, 9 6. Herfried Hoinkes—p.10 7. Hans Almann—p.10 8. Karl Christian Wallen—p.10 9. Walter Schawarzacher—p.11, 14 10. Bullock Workman—p.11 11. Heinrich Herald—p.12 12. Walter Brendel—p.13 13. Alfred Hoikes—p.13 14. Colin Bull—p.14 15. David Elliott—p.14 16. Robert Sharp—p.14, 15 17. Bert Crary—p.15, 17, 89 18. Mildred Crary—p.19 19. Harry Wexler—p.15, 16 20. Richard Hubley—p.16, 23 21. Chuck Sterns—p. 17 22. Phil Church—p.18, 22, 31, 41, 42, 108 23. Arne Hansen—p.18, 20, 35, 36, 38, 43, 46 24. Joe Fletcher—p.19, 57, 60, 70, 90, 91 25. Father Tom Cunningham—p.19 26. Fritz Awe—p.19, 23, 28 27. Morris Davidson—p.20, 77 28. Ken Hunkins—p.20, 22, 28, 37, 38, 39, 40, 56, 57 29. Terrence McDonald—p.20, 84 30. Lt. Colonel Stromquist—p.20 31. Joe Smith—p.20 32. Joseph Bilotta—p.20 33. Brian Freeman—p.20, 21 34. John Sader—p.24 35. Charlie Keeler—p.24 36. Tom English—p.26, 37 37. Frank Badgley—p.28 38. Bill Campbell—p.29, 36 39. George Cvijanovich—p.35 40. Walfried Ekman—p.38, 39, 40 41. Wieland Bieckness (?)—p.39 42. Hal Brayton—p.43 43. Max Brewer—p.44, 45, 53 44. Art Leckenbrook—p.46 45. Lawson Brigham—p.47 46. Major Joe Belota—p.48, 49 47. Jack Calvert—p.49 48. Sir Hubert Wilkins—p.52, 53 49. Lowell Thomas Sr.—p.52, 53, 54 50. Peter Froekin—p.52, 53 51. Bernt Balchen —p.53, 54 52. Prof. Charles Raymond—p.55 53. Allen Thorndike—p.55, 70, 71, 80 54. Gary Baker—p.55 55. Sam Kolbeck—p.55 56. Walt Whitman—p.55, 92 57. Admiral Bowen —p.57 58. Richard Goodie—p.58 59. Suki Manave—p.58, 62 60. Brooks Brian—p.58 61. Ned Ostenso—p.58, 62, 74 62. Bill Swenbeck—p.58 63. Dick Waters—p.59 64. Ross Burent—p.59, 60 65. Kurt Bryan—p.62, 63 66. Bert Boleen—p.63 67. John Kutzba—p.63 68. Joe Smagerinski—p.63 69. Jule Charney—p.63 70. Admiral Tom Owen—p. 65, 66, 67 71. Brian Shoemaker—p.1, 52, 64, 68, 69, 100 72. Dick Schauss—p.68, 69 73. Admiral ...